2001
DOI: 10.1046/j.1365-2958.2001.02358.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale monitoring of pleiotropic regulation of gene expression by the prokaryotic nucleoid‐associated protein, H‐NS

Abstract: Despite many years of intense work investigating the function of nucleoid‐associated proteins in prokaryotes, their role in bacterial physiology remains largely unknown. The two‐dimensional protein patterns were compared and expression profiling was carried out on H‐NS‐deficient and wild‐type strains of Escherichia coli K‐12. The expression of approximately 5% of the genes and/or the accumulation of their protein was directly or indirectly altered in the hns mutant strain. About one‐fifth of these genes encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
375
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(397 citation statements)
references
References 69 publications
18
375
0
4
Order By: Relevance
“…All strains are F Ϫ . References or sources for the mutations that were introduced by transduction into the strains are as follows: rho(A243E) (interchangeably also designated as rho-4) and nusG(G146D) (27); hns-1001::Kan (Tn5seq1 insertion in codon 20 of hns) (28); and hns-205::Tn10 (Tn10 insertion in codon 92 of hns) (19). The ⌬pcnB, ⌬stpA, ⌬hha, and ⌬ydgT mutations were introduced as Kan r deletioninsertion mutations from the Keio knockout collection (4) and, where necessary, the Kan r marker was then excised by site-specific recombination with the aid of plasmid pCP20, as described previously (17 (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…All strains are F Ϫ . References or sources for the mutations that were introduced by transduction into the strains are as follows: rho(A243E) (interchangeably also designated as rho-4) and nusG(G146D) (27); hns-1001::Kan (Tn5seq1 insertion in codon 20 of hns) (28); and hns-205::Tn10 (Tn10 insertion in codon 92 of hns) (19). The ⌬pcnB, ⌬stpA, ⌬hha, and ⌬ydgT mutations were introduced as Kan r deletioninsertion mutations from the Keio knockout collection (4) and, where necessary, the Kan r marker was then excised by site-specific recombination with the aid of plasmid pCP20, as described previously (17 (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…H-NS is thought to interact unspecifically with DNA, although it prefers intrinsically curved binding sites [Dame et al, 2001], and it was shown to act as global regulator controlling the expression of more than 200 genes in E. coli [Hommais et al, 2001]. The mechanism by which H-NS influences RNA polymerase activity is not fully understood.…”
Section: Mechansims Of Nucleoid Organizationmentioning
confidence: 99%
“…Highlighting the importance of the AR2 system is the plethora of regulators involved in its regulation, the relative importance of each regulator depending on environmental pH and growth phase. These regulators include: two phosphorelays, EvgAS (Masuda & Church, 2002) and TorRS (Bordi et al, 2003), the stationary phase s s -factor (De Biase et al, 1999), the global regulators Crp ) and H-NS (Hommais et al, 2001), three AraC-like regulators, GadW (Ma et al, 2002), GadX (Shin et al, 2001) and YdeO (Masuda & Church, 2003), and the Era-like GTPase TrmE (Gong et al, 2004). Central to the AR2 system is the activity of the LuxRlike transcription regulator GadE, as most of the regulators listed target gadE expression.…”
Section: Introductionmentioning
confidence: 99%